2006
DOI: 10.1149/1.2358103
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Controlling the Size of Gold Nanoparticles

Abstract: This work demonstrates the electrochemical synthesis of nanoscale gold particles using a surfactant solution. Tetradodecylammonium bromide ͑TTAB͒ surfactant was applied to stabilize the gold clusters. Experimental results reveal that the size of the produced gold nanoparticles is controlled by the amount of TTAB surfactant, the current density, and the growth temperature. The size of the gold nanoparticles can be controlled in the range 58.3-8.3 nm. The particle size decreases as the amount of TTAB increases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 39 publications
1
44
0
2
Order By: Relevance
“…In case of Pd-NPs, the electrolysis was proven to afford for a tight control over the core size and the experimental results were in good agreement with the fundamentals of electrocrystallization theory [42,46]. Recently, Huang et al [47] studied SAE processes carried out in the presence of a mixture of surfactants and demonstrated that the size of electrosynthesized Au-NPs can be controlled by the nature and relative amount of the surfactants, by the electrochemical parameters employed during the SAE preparation, and by the synthesis temperature.…”
Section: Introductionmentioning
confidence: 81%
“…In case of Pd-NPs, the electrolysis was proven to afford for a tight control over the core size and the experimental results were in good agreement with the fundamentals of electrocrystallization theory [42,46]. Recently, Huang et al [47] studied SAE processes carried out in the presence of a mixture of surfactants and demonstrated that the size of electrosynthesized Au-NPs can be controlled by the nature and relative amount of the surfactants, by the electrochemical parameters employed during the SAE preparation, and by the synthesis temperature.…”
Section: Introductionmentioning
confidence: 81%
“…Afterwards, nitrogen gas (Kaohsiung, Taiwan) was used to dry it. As reported earlier [19,20], the GNPs were prepared via the electrochemical method. GNPs were dispersed into the aqueous solution of PEDOT:PSS in an optimized ration as a HTL.…”
Section: Introductionmentioning
confidence: 99%
“…Single cell manipulation can be realized using OT (Cheah et al, 2014;Moffitt et al, 2008;Roy et al, 2014). Optical dielectrophoresis (ODEP) is another approach to realize a flexible manipulation of particles and cells (Huang et al, 2012(Huang et al, , 2013Liang et al, 2012). Despite impressive performances of such optics-based manipulating techniques, they generally require bulky, complicated optical setups, which are difficult to be miniaturized.…”
Section: Introductionmentioning
confidence: 99%